Babae, utang mo-- [dollar]26 bilyon? - Aguilar, Mila D.; Canada Fund.; Institute for Filipino Cinema ([Quezon City] The Institute, 1990)
An interview with women experts, activists, and people on the streets about foreign debt and how it affects the Filipino women
VHS
Katuwang sa paglikha/taga-interbyu, Ma. Ernie Selvido; editor, Judy Flores.
Keywords: Debts, External -- Philippines; Women -- Social conditions. -- Philippines; Sociology